(untitled) - Flynn, Ida M. (Boston, MA, 2006)
This fourth edition blends operating systems theory and practice in a well-organized way. Its innovative two-part approach explores operating systems theory and development in the first section, and discusses the four most widely-used operating systems (MS-DOS, Windows, Linux, and UNIX) in the second. Each chapter has been updated for currency, and a brand-new chapter on System Security has been added
Keywords: Operating systems ( Computers )